Computer science programming basics in Ruby - Frieder, Ophir (O'Reilly, 2013)
Annotation
Includes bibliographical references. - Print version record
Keywords: Ruby (Computer program language); Computer programming; Ruby (Langage de programmation); Programmation (Informatique); computer programming; COMPUTERS; Database Management; General; COMPUTERS; Desktop Applications; Databases; COMPUTERS; System Administration; Storage & Retrieval